2013
DOI: 10.5414/cp201969
|View full text |Cite
|
Sign up to set email alerts
|

Adherence in tamoxifen therapy after conversion to a rebate pharmaceutical in breast cancer patients in Germany

Abstract: This analysis underlines an association between the initiation of rebate contracts and a negative impact on the compliance of breast cancer patients on an adjuvant hormonal treatment The impact of rebate contracts on the health of patients and the health care costs should be evaluated in further therapeutic fields through additional research projects. *both authors contributed equally to the manuscript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…Five studies showed that odds of persistence increased by 21%–66% if treatment was received by an oncologist or a gynecologist as opposed to a general practitioner, 32 , 43 45 , 53 while two studies found no significant effect. Five studies found that being prescribed more medications per month was associated with increased odds of persistence; 7 , 25 , 26 , 54 , 55 however, an additional study showed the opposite effect 32 and three studies found no significant effects.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Five studies showed that odds of persistence increased by 21%–66% if treatment was received by an oncologist or a gynecologist as opposed to a general practitioner, 32 , 43 45 , 53 while two studies found no significant effect. Five studies found that being prescribed more medications per month was associated with increased odds of persistence; 7 , 25 , 26 , 54 , 55 however, an additional study showed the opposite effect 32 and three studies found no significant effects.…”
Section: Resultsmentioning
confidence: 97%
“…Three studies found that a codiagnosis of osteoporosis or diabetes was related to increased persistence. 43 45 However, mixed results were found for the effects of comorbidities in general, with the majority of studies finding no significant associations.…”
Section: Resultsmentioning
confidence: 99%
“…This study suggested that side effects can cause women to discontinue treatment, which has been shown in several quantitative studies (Demissie et al ., ; Simon, Latreille, Matte, Desjardins, & Bergeron, ; Wouters et al ., ). However, there is an inconsistent relationship between side effects and adherence, with some studies finding no significant effects (Fink et al ., ; Kostev et al ., ). The results from this study suggest that adherence is not just related to the experience of side effects, but how women weigh these up against their beliefs; that is that just the experience of side effects is not sufficient to cause non‐adherence.…”
Section: Discussionmentioning
confidence: 97%
“…Another point to be mentioned is the introduction of rebate contracts in the German healthcare system, which has not only significantly increased the level of bureaucracy in pharmacies but also posed a range of new patient safety risks. [28][29][30] Therefore, a new tool was introduced in 2008, enabling pharmacists and PTAs to deny substitution of the prescribed medicine by raising pharmaceutical concerns about rebate contract product's dosage form appropriateness, its potential negative impact on patient's adherence, etc. 18 However, the risk of abstaining from using the aforementioned tool when necessary was rated rather highly.…”
Section: Discussionmentioning
confidence: 99%